Toward a Poetics and Pedagogy of Sound: Students as Production Engineers in the Literature Classroom - Karen Lee Osborne (Journal of the Assembly for Expanded Perspectives on Learning, 2016)
Pairing students to be recorders and production editors of poetry readings results in a collaborative assignment that embodies students’ experience of reading through media.